Conversion of HPV 18 positive non-tumorigenic HeLa-fibroblast hybrids to invasive growth involves loss of TNF-α mediated repression of viral transcription and modification of the AP-1 transcription complex - Soto, Ubaldo; Lengert, Maike; Finzer, Patrick; Zur Hausen, Harald; Rösl, Frank (Oncogene, 1999)
AP-1 represents a transcription factor, which plays a pivotal role in initiating and maintaining the expression of human papillomavirus (HPV) oncoproteins E6 and E7 during HPV-linked carcinogenesis of the uterine cervix. AP-1 stands as a synonym for different proteins such as c-Jun, JunB, JunD, c-Fos, FosB as well as the Fos-related antigens Fra-1 and Fra-2, which can either homo- or heterodimerize to build up a functional transcription complex. AP-1 is mainly considered as a positive regulator, which binds to cognate DNA sequences within the viral upstream regulatory region. By using non-tumorigenic HeLa-fibroblast hybrids (`444'), their tumorigenic segregants (`CGL3') as well as HPV 18 positive HeLa cells as a experimental model system, evidence is provided that AP-1 composition differs considerably between these cell lines. In nuclear extracts obtained from non-tumorigenic cells, Jun-family members (in the order c-Jun>JunD>JunB) were mainly heterodimerized with Fra-1, a protein, known to be involved in the abrogation of AP-1 activity under certain experimental conditions. In contrast, Fra-1 concentration is low in extracts from tumorigenic cells. Conversely, c-Fos, the canonical dimerization partner of Jun proteins is expressed in substantial quantity in HeLa- and `CGL3' cells, but it is completely absent in AP-1 complexes from non-tumorigenic `444' cells. Ectopical expression of c-fos under a heterologous promoter in `444'-cells induces tumorigenicity and a change of the Jun/Fra-1 ratio towards a constellation initially detected in `CGL3'-and HeLa cells. Furthermore, conversion to tumorigenicity is accompanied with a resistance against TNF-α, a cytokine, capable to selectively suppress HPV 18 transcription in formerly non-malignant cells. These data propose a novel role for AP-1 as an essential component of an inter- and intracellular surveillance mechanism negatively controlling HPV transcription in non-tumorigenic cells.
Gesehen am 30.01.2019